Integration of the latest Digital Terrain Model (DTM) with Synthetic Aperture Radar (SAR) Bathymetry - Atriyon Julzarika; Trias Aditya; S Subaryono; H Harintaka; Ratna Sari Dewi; Luki Subehi (Brawijaya University, 2021)
Topography and bathymetry integration is one of the essential things in providing height data. So far, the topography and bathymetry problems are the lack of height data availability, not up to date, and low vertical accuracy. The latest DTM is one of the topography data with up to date elevation with a spatial resolution of 5 m. Bathymetry extracted from SAR images. It is an alternative depth data for ocean bathymetry and inland water bathymetry. Topography and bathymetry integration is required to obtain comprehensive height data. This study aimed to integrate the latest DTM with SAR bathymetry. The method used in this integration was DEM integration. The method combined the latest DTM data with SAR bathymetry based on the correlation of the two data's standard deviation. The integration of the latest DTM with SAR bathymetry needs to consider differences in height reference fields. Two integration studies were conducted in this research-the latest DTM integration with ocean bathymetry for Rote Island. Then the integration of the latest DTM with inland water bathymetry in Lake Singkarak. The result of the integration is necessary to check the surface by generating longitudinal and cross-section profiles. Integrating the latest DTM and SAR bathymetry can be used for various mapping surveys on lands and waters.